Pro-ecological Attitudes and Expectations of the Inhabitants of Villages Situated in Protected Areas - Perepeczko, Barbara (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2010)
The article comprises a presentation of selected results of studies over the ecological awareness of the inhabitants of villages situated in the communes covered by the Natura 2000 network. The first part of the article deals with the distribution of the indicator of pro-ecological attitudes, which helps reveal the categories of inhabitants who are particularly sensitive to and who have considerable knowledge of matters relating to the natural environment. The second part presents their opinions on the condition of the local environment. The surveyed persons are the proponents of the protection of the natural environment in the areas they live in and they are aware of the beauty of these areas. They believe that the attitudes and behaviours of local residents, and the activity of local authorities are decisive for the condition of the surrounding environment. They also think that restrictions connected with environmental protection ought to be compensated for in the form of special – but not only financial, privileges. The opinions of the surveyed villagers are not always consistent and they do not always find confirmation in their behaviours.
Keywords: natural environment; protected areas; pro-ecological attitude; inhabitants of villages; local authorities; restrictions; opinions; actions